HUBUNGAN SELF EFFICACY DENGAN QUALITY OF LIFE PADA PASIEN SESUDAH STROKE - Pongantung, Henny; Anita, Fransiska; Palango, Charlos; Manuel, Claudio (Universitas Islam Negeri Alauddin Makassar, 2020)
Stroke is a disease that can cause the first number of disabilities and their events occur suddenly, which can cause severe disability or death. The disability has an effect on the psychological state so that it can experience depression with symptoms of feeling helpless, ashamed of the situation which can result in quality of life decreased. Many factors affect the quality of life, one of which is self efficacy. Self efficacy is the most important factor that is very influential on stroke patients. Someone with high self efficacy can increase higher motivation so they have the desire to recover quickly. This study aims to determine the relationship between self efficacy and quality of life in patients after stroke. This research is an observational analytic with study cross sectional design.The sampling method using non-probability sampling techniques through consecutive sampling , amounting to 76 respondents. The instrument used was in the form of a questionnaire, the test used in this study was the statistical test chi-square because there was a value of count <5 and anvalue of expected count> 20% then continued with the merging of cells so that the table changed to 2x2 and the value of p = 0,000 was obtained with the level significance of α = 0.05 which is read in Fisher's Exact Test. This shows that the value of p <α means that there is a relationship of self efficacy with quality of life in patients after stroke in the South Sulawesi Provincial Hospital. It is expected that patients after stroke have high self efficacy so they can act in a positive direction in order to improve their health status so that the quality of life also increases Keywords: Self Efficacy, Quality Of Life, Stroke